Gambaran Motivasi Belajar Siswa dari Keluarga yang Broken Home - Harnita, Dina Yudi; Zikra, Zikra (Lembaga Yasin AlSys, 2023)
Every teenager wants to live in a complete family. However, not all teenagers are lucky to have it, such as family divorce. broken home Families can affect teenagers' learning at school. This research aims to describe the learning motivation of students from broken home families. This research uses quantitative methods with a descriptive approach. The sample for this research was 56 students using a purposive sampling technique using the criteria of young victims of broken homes and looking at the students' behavior and achievements at school. Data were collected using a learning motivation questionnaire consisting of aspects of learning preparation, aspects of following the teaching and learning process, and aspects of following up on lessons with a Likert model scale. The number of validity items is 30 items and the reliability is 0.884. To find out the description of the research variables, use the percentage formula. The results of this research found that 43.10% of students from broken home families had low learning motivation. Therefore, guidance and counseling services are needed, such as information services, content mastery services, individual counseling services and group guidance services to increase student learning motivation.